Modifikasi Media Tanam Tanah Terinfeksi Ganoderma pada Pembibitan Kelapa Sawit di Pre Nursery - Nugroho, Agung; Yollanda, Resty Fadhillah; Iqbal, Muhamad; Utomo, Yuyut Budi; Nurliana, Nurliana (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
Nursery planting media in smallholder oil palm plantations that are attacked by stem rot disease caused by Ganoderma sp do not receive special attention and it is not uncommon for farmers to use land around their oil palm plantations that is attacked by Ganoderma. This research aims to modify planting media infected with Ganoderma spp with Trichoderma spp input in the planting media for oil palm (Elaeis guineensis Jacq.) nurseries in the Pre-Nursery. The research was conducted in the Greenhouse of the Indonesian Palm Oil Technology Institute in March 2024. Planting media material from the Ganoderma-infested People's palm oil plantations was taken from Kwala Pesilam village, Padang Tualang sub-district, Langkat district, North Sumatra Province. The design used in the research was a non-factorial Randomized Design with 5 (five) treatment levels, namely T01 (positive control) using soil infected with Ganoderma spp, T02 (negative control) using sterile soil, T1 = 5 grams of Trichoderma, T2 = 10 grams of Tricodherma and T3 = 15 grams of Trichoderma. The research results the application of Trichoderma 10 g/seed doses gave good results on average growth of oil palm seedlings and diseasesin seedlings are dominates by anthacnose